A New Dynamic Model for Sealed Coring Saturation Correction in Hydrocarbon Reservoir. (9th October 2017) - Tu, Bin; Li, Jie
Abstract : It is one of the most intuitive methods to analyze the formation of oil and water saturation by sealed coring. But this method is affected by a variety of factors, such as pore volume change, fluid compression, and separation of dissolved gas. In view of the impact of such factors on sealed coring test saturation, there are four kinds of correlation methods currently, namely, comprehensive coefficient correction method, experiment correlation method, mathematical statistics method, and mathematical model correction method, with their own advantages and disadvantages. Based on the analysis of physical change during core lifting process, this paper proposes the mathematical model for dynamic correction of core saturation based on dissolved gas drive filtration theory, multiphase flow fractional flow theory, and corresponding work flow. This method comprehensively considers the impact of relative permeability of three-phase fluid flow, elastic compression nature of fluid and rock, fluid viscosity, volume factor, solution GOR, and other high-pressure PVTs, so it features a wider adaptability, and the accuracy of model correction results satisfies the project requirements. This method provides a reliable basis for the true oil-water saturation of actual reservoir and has an important theoretical and practical significance.